Evaluating outcomes of patient-centered enhanced recovery after surgery (ERAS) in percutaneous nephrolithotomy for staghorn stones: An initial experience - Lei, Jun; Huang, Kai; Dai, Yingbo; Yin, Guangming (Frontiers in Surgery, 2023)
Objective: To evaluate the outcomes of patient-centered enhanced recovery after surgery (ERAS) in percutaneous nephrolithotomy (PCNL) for staghorn stones. Patients and methods: A retrospective analysis of 106 patients with staghorn calculi who underwent PCNL treatment at the Third Xiangya Hospital from October 01, 2018 to September 30, 2021 was performed. The patients were divided into the ERAS group (n=56) and traditional group (n=50). The ERAS program focused on a patient-centered concept, with elaboration on aspects, such as patient education, nutritional support, analgesia, body warming, early mobilization, nephrostomy tube removal, and strict follow-up. Results: The total stone free rate and total complication rate were similar in both groups. The visual analogue scale (VAS) 6 hours after surgery, ambulation off bed time, indwelling ﬁstula time, indwelling catheter time, and postoperative hospital stays were lower in the ERAS group than in the traditional group (P <0.05). The multiple session rate in the ERAS group (19, 28.57%) was lower than that in the traditional group (30, 60%) (P = 0.007). The 1-year stone recurrence rate in the ERAS group (7, 17.5%) was lower than that in the traditional group (14, 38.9%) (P = 0.037). Conclusion: The patient-centered ERAS in PCNL for staghorn stones accelerated rehabilitation by relieving postoperative pain, shortening hospitalization time, accelerating early ambulation, and reducing multiple session rate and 1-year stone recurrence rate, which have socioeconomic benefits.